El pensamiento griego en la lógica de Ibn Hazm. Su Kitab al-taqrib - Ramón Guerrero, Rafael (Anales del Seminario de Historia de la Filosofía, 2002)
The first book consecrated to logic, written by an andalusian author is Ibn Hazm’s Kitªb al-taqrÌb li-Êadd al-manðiq (“Introduction to definition of logic”). Where, the author seeks to adapt the logic to the simple language of the jurists. Here it is pointed out how this important treatise can depend on the logical school of Bagdad.